2021
DOI: 10.1101/2021.11.30.21266756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of subcutaneous or intravenous route of administration of casirivimab and imdevimab monoclonal antibodies with clinical outcomes in COVID-19

Abstract: ImportanceMonoclonal antibody (mAb) treatment decreases hospitalization and death in outpatients with mild to moderate COVID-19; however, only intravenous administration has been evaluated in randomized clinical trials of treatment. Subcutaneous administration may expand outpatient treatment capacity and qualified staff available to administer treatment, but association with patient outcomes is understudied.ObjectiveTo evaluate whether or not, i.) subcutaneous casirivimab and imdevimab treatment is associated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 8 publications
5
11
0
Order By: Relevance
“…Importantly, treatment with CAS+IMD appeared to have a benefit on mortality in the CDM cohort, as the 30-day estimated risk of death was much lower in the treated than untreated patients. These results further support the public health implications of this therapy, and are consistent with the real-world studies that also suggested lower mortality in patients who received mAb treatment [9,11,15,16], albeit in variants susceptible to such therapy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Importantly, treatment with CAS+IMD appeared to have a benefit on mortality in the CDM cohort, as the 30-day estimated risk of death was much lower in the treated than untreated patients. These results further support the public health implications of this therapy, and are consistent with the real-world studies that also suggested lower mortality in patients who received mAb treatment [9,11,15,16], albeit in variants susceptible to such therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Evidence from several real-world studies suggests that appropriate treatment with CAS+IMD was associated with an incidence of hospitalizations that may be 50%-90% lower than among untreated patients [4,5,8,9,16,23]. The magnitude of effects observed in the current study fell within that range and, additionally, demonstrated greater benefits among those at higher risk.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Such activity was previously suggested by in vitro studies 5,13-16 and smaller real-world studies that reported its effectiveness for reducing all-cause hospitalization or mortality. 30,31…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] In vitro studies suggested that CAS+IMD retains neutralization activity against most VOC including Delta but with the exception of Omicron (B.1.1.529). 5,[13][14][15][16][17] Most real-world studies assessing the effectiveness of CAS+IMD for treating COVID-19 [18][19][20][21][22][23][24][25][26][27][28][29][30] were conducted prior to Delta, and those that did overlap with the emergence of the Delta variant were single-center and of small sample size. 19,30,31 Furthermore, with the introduction of COVID-19 vaccines, an improved understanding of vulnerable groups, and the emergence of the Delta variant, it became important to evaluate the effectiveness of CAS+IMD across these patient subgroups.…”
Section: Introductionmentioning
confidence: 99%